African American Women Faculty in the Historically White University: Learning to Negotiate the Academy - Nicole M. Ray (Adult Education Research Conference, 2008)
African American women faculty continue to encounter obstacles and challenges to developing successful careers at historically White, research intensive universities. This research project addresses how successful African American women faculty learn to negotiate the academic responsibilities of research, teaching and service. Study participants report that learning from previous experiences in the family, community and other work environments, mentoring and other communal relationships are significant in negotiating their academic duties.